Crystal Growth of Multifunctional Borates and Related Materials - Leonyuk, Nikolay I (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Borate crystals are attractive for different technological applications because of their favorable physical and chemical properties like stability and high transparency, both high thermal and non-linear optical coefficients, making them ideal active media for highly efficient solid state lasers. In this Special Issue, different aspects of multifunctional borate crystals are discussed, including ortho- and oxyorthoborates and compounds with condensed anions, as well as their nonlinear optical and laser properties and piezoelectric characteristics. For this reason, complex investigations of the phase relationships in multi-component borate melts, the study of crystal growth conditions of novel high-temperature borates, and the development of the “crystallization conditions, composition, structure, and properties” concept will provide a scientific basis for growth technologies of high performance electronic and optical devices and components with a variety of industrial, medical and many other applications. In the meantime, these relationships can help to estimate the affinity of synthetic borate materials with their natural prototypes and structural analogues.